Iodine Intake in Portuguese School Children - Limbert, Edward; Prazeres, Susana; São Pedro, Márcia; Madureira, Deolinda; Miranda, Ana; Ribeiro, Manuel; Carrilho, Francisco; Jácome de Castro, J; Lopes, Maria Santana; Cardoso, João; Carvalho, Andre; Oliveira, Maria João; et al. (Acta Médica Portuguesa, 2012)
Objective: The aim of the present study was to evaluate iodine intake in portuguese school children in order to inform health authorities of eventual measures to be implemented. Introduction: Iodine is the key element for thyroid hormone synthesis and its deficiency even mild, as found in other European countries, may have deleterious effects in pregnancy resulting in cognitive problems of offsprings. In Portugal there are no recent data on iodine intake in schoolchildren. Population and methods: 3680 children aged 6-12 years of both sexes, from 78 different schools were studied. Iodine intake was evaluated trough urine iodine (UI) determinations using a colorimetic method. Results: The global median UI value was 105.5µg/L; the percentage of children with UI <100µg/L was 47.1%, corresponding to 41% of the studied schools. The percentage of values <50µg/L was 11.8%. The male gender, the south region of the country and the distribution of milk in school were significantly linked with a higher iodine elimination. Discussion: Our global results point to a borderline/ mildly insufficient iodine intake in the portuguese school population. However 47% of the children had UI under 100 µg /L. The comparison of our results with the available data from 30 years ago, point to a considerable improvement, due to silent prophylaxis. Male gender, geographical area and milk distribution influenced positively iodine intake.The importance of milk has been refered in numerous papers. Conclusions: The study of UI in the Portuguese school population points to a borderline iodine intake. However, in 47% of children iodine intake was inadequate. Compared with data from the eighties, a considerable increase in iodine elimination was found. Taking into account the potencial deleterious effects of inadequate iodine intake, a global prophylaxis with salt iodization has to be considered.